2015
DOI: 10.1002/ajpa.22837
|View full text |Cite
|
Sign up to set email alerts
|

Bipedality from locomotor autonomy to adulthood in captive olive baboon (Papio anubis): Cross‐sectional follow‐up and first insight into the impact of body mass distribution

Abstract: Our results suggest a close relationship between the pattern of mass distribution and the mechanism of balance control in the spontaneous bipedal walking of baboons. The mechanical effects of the pattern of mass distribution on the ability to perform bipedally in extant nonhuman primates are discussed in the context of the evolution toward habitual bipedalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…Druelle et al. (2016b) observed that olive baboons, Papio anubis , with a relatively heavier trunk walk bipedally for longer periods than those with lighter trunks. Kimura () showed the importance of lifting the centre of gravity to provide a sufficient amount of energy recovery in chimpanzees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Druelle et al. (2016b) observed that olive baboons, Papio anubis , with a relatively heavier trunk walk bipedally for longer periods than those with lighter trunks. Kimura () showed the importance of lifting the centre of gravity to provide a sufficient amount of energy recovery in chimpanzees.…”
Section: Discussionmentioning
confidence: 99%
“…The trunk region has been shown to be a fundamental component of bipedal balance in primates, so theoretically an elongated and larger trunk should increase its mass MI, therefore stabilizing the upper body against the movements of the hindlimbs (Preuschoft, 2004). Druelle et al (2016b) observed that olive baboons, Papio anubis, with a relatively heavier trunk walk bipedally for longer periods than those with lighter trunks. Kimura (1996) showed the importance of lifting the centre of gravity to provide a sufficient amount of energy recovery in chimpanzees.…”
Section: Differences In Inertial Variablesmentioning
confidence: 99%
“…(), as previously applied to baboons (Raichlen, , ; Druelle et al. ). External linear measurements of the nine body segments were taken (head, including the neck, trunk, upper arm, forearm, hand, thigh, shank, foot and tail).…”
Section: Methodsmentioning
confidence: 99%
“…Our measurement protocol allows the use of the geometric model developed by Crompton et al (1996), as previously applied to baboons (Raichlen, 2004(Raichlen, , 2005bDruelle et al 2016a). External linear measurements of the nine body segments were taken (head, including the neck, trunk, upper arm, forearm, hand, thigh, shank, foot and tail).…”
Section: Collecting Morphometricsmentioning
confidence: 99%
“…Simultaneously, infant baboons (i.e., 0–2 years of age) undergo drastic changes in their pattern of mass distribution. Initially, in comparison to older individuals (i.e., juveniles and adults), they possess a relatively heavy head, a light trunk, and heavy hands and feet [Altmann et al, ; Druelle et al, ; Leigh et al, ]. With development, more mass becomes allocated to the proximal limb segments [Raichlen, ].…”
Section: Introductionmentioning
confidence: 99%